Strain behavior of the hydrogenated submicrocrystalline Ti–6Al–4V alloy; Russian Physics Journal; Vol. 54, iss. 6 - Stepanova E. N. Ekaterina Nikolaevna; Grabovskaya G. P. Galina Petrovna; Zabudchenko O. V. Olga Vyacheslavovna; Mishin I. P. Ivan Petrovich (Condensed-State Physics, 2011)
Title screen